Islamic perspective: the aesthetics of plants in the built environment - Abu Bakar, Aniza (IIUM Press, 2015)
This chapter attempts to discuss on one of the natural elements of the environment, which is vegetation by focusing on its physical aesthetical values and functional aspect that benefits the environment as a whole. Islamic perspective is also being emphasised as to briefly relate to the hard-sciences and the revealed knowledge. This is seen as an important aspect as a person needs to be drawn back to the creator while realising the reasons of Allah SWT creations as some might be too amazed by the advancement of the current technology that they forget the ultimate power behind it.